Analisis Faktor-Faktor Yang Memengaruhi Kualitas Laba Setelah Penerapan International Financial Reporting Standard (IFRS) - Bonna Marietta Bardo; Akhmad Saebani; Andi Manggala Putra (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
This study is a quantitative study that aims to find out the factors that influence earnings quality after IFRS implementation. The dependent variable in this study is earnings quality measured by the calculation of discretionary accruals. And the independent variable for this research is company size measured using the natural logarithm of total assets, profitability using ROA and capital structure using DAR. The sample used was at property and real estate companies listed on the Indonesia Stock Exchange as many as 55 companies in 2012-2018. The sampling technique used in this study was by purposive sampling, which is the technique of determining the sample by considering a certain thing based on relevant criteria if it is associated with the research. The data analysis method used is a fixed effect regression model. Data processing in this study uses STATA. This study uses agency theory to strengthen research. The results showed that company size, profitability and capital structure had a significant positive effect on earnings quality.